Rural Community Life and the Importance of Reciprocal Survival Strategies - Meert, Henk (Sociologia Ruralis, 2000)
Although Belgian poverty is mainly concentrated in urban regions, the profound restructuring of labour and food markets, the dismantling of the welfare state and the growth of new types of households are also producing poverty and social exclusion in rural areas. This paper stresses that not every deprived rural household should be regarded as excluded from society. By developing survival strategies, households attempt to escape from social marginalization. To understand these responses, a typology of survival strategies is constructed, based on Polanyi’s spheres of economic integration (market exchange, redistribution and reciprocity). These survival strategies, including agricultural and non-agricultural activities, are analysed in relation to the Hageland,a peripheral rural area in Flanders. Based upon Doreen Massey’s geological metaphor, the current potentials and obstacles embedded in the historical layers of the socio-spatial structure of the area, are assessed. By comparing the results of this research with similar research amongst urban households, some particularities of rural poverty are distinguished.
Sociology
Keywords: Belgium; economic integration; poverty; urban poverty

Sustainable Agriculture in the United States and France: A Polanyian Perspective - Barham, Mary Elizabeth (2000)
Sociology
Keywords: France; social movements; sustainable agriculture

Three Pillars of Welfare State Theory: T.H. Marshall, Karl Polanyi and Alva Myrdal in Defence of the National Welfare State - Holmwood, John (European Journal of Social Theory, 2000)
Current social and political theory is sceptical of the future of welfare states in the face of global markets. Their moral claims, too, have been challenged by the neo-liberal association of market capitalism and individual freedom and by an implicit acceptance of that critique - of the welfare state as bureaucratic - by left-wing commentators. This article offers a defence of the national welfare state as the guarantor of 'complex freedom'. This defence is derived from the theoretical contributions of Marshall, Polanyi and Myrdal and offers a reconsideration of the debate immediately after the second world war over the welfare state and its relevance today. Marshall's concept of social rights has become a familiar part of our own debate, but it is argued that Polanyi provides the rigorous critique of market relationships which is missing, and Myrdal locates gender issues as central to the understanding of welfare state development and women's rights as integral to social rights.
Sociology
Keywords: economic policy; gender; globalization; government policy; human rights; markets; public welfare; social & economic rights; social rights; welfare; welfare economics